'It's like, we are thankful. But in the other way…they are just killing us too': community members' perspectives of the extractives industry's funding of recreational and cultural programmes in Fort McKay, Alberta. Issue 1 (2nd January 2020) - van Luijk, Nicolien; Giles, Audrey R.; Frigault, Julia; Millington, Rob; Hayhurst, Lyndsay M. C.
ABSTRACT: The growing role of the extractives industry in providing funding for recreational and cultural programmes in exchange for access to Indigenous lands raises some important questions about the impact this has on local community members. Informed by tenets of postcolonial theory and a community-based participatory research methodology, we worked with individuals in a small Indigenous community, Fort McKay, Alberta, Canada, to learn about their perspectives of the role of industry in funding their recreational and cultural programmes. Our findings revealed that while many were grateful for this funding, they also felt that industry had a responsibility to fund these programmes to offset the negative impacts industry had on their traditional territories. Further, they felt that the provision of these programmes does not fully address the loss of access to traditional cultural practices. While proponents of the extractives industry promote funding as a way to increase Indigenous self-determination, our findings show that increased self-determination through such arrangements is limited.